Bayesian statistical approach to binary asteroid orbit determination. Issue Volume 10:Issue S318(2015) (1st March 2016) - Kovalenko, Irina D.; Stoica, Radu S.; Emelyanov, N. V.; Doressoundiram, A.; Hestroffer, D.
Abstract: The problem of binary asteroids orbit determination is of particular interest, given knowledge of the orbit is the best way to derive the mass of the system. Orbit determination from observed points is a classic problem of celestial mechanics. However, in the case of binary asteroids, particularly with a small number of observations, the solution is not evident to derive. In the case of resolved binaries the problem consists in the determination of the relative orbit from observed relative positions of a secondary asteroid with respect to the primary. In this work, the problem is investigated as a statistical inverse problem. Within this context, we propose a method based on Bayesian modelling together with a global optimisation procedure that is based on the simulated annealing algorithm.